PHYTOREMEDIATION OF IRON CONTAMINATED SOIL BY WATERLEAF (Talinum triangulare (Jacq) Willd) IN JOS, PLATEAU STATE, NIGERIA - OWONUBI, AYODELE; OREWERE, EMMAMOGE; LOHNAN, NANLOH (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
Phytoremediation is an environmentally friendly approach which involves plants for removal of contaminants from polluted soil. The objective of this study therefore was to evaluate the effectiveness of water leaf (Talinum triangulare) in extraction of iron (Fe) from contaminated soil. The research consisted of the following treatments: 0, 26, 52, 78, 104, 130 and 156 Fe mg/kg of soil. Iron nitrate was used as the source of iron. The plant data collected were leaf and flower count, plant height, stem diameter, number of branches, shoot weight, the root weight and iron concentration in the shoot. These were analyzed using analysis of variance and the Fisher’s pairwise comparisons. The result showed that there was no significant effect of treatments on growth parameters except for leaf count. Plants that received 130 (Fe mg/kg) had significantly higher leaf count probably due to higher amount of nitrogen supplied by iron nitrate. There was significance difference in iron concentration in the shoots of water leaf plants among the various treatments when compared to the control. Mean maximum extraction of iron was 5815 mg/kg with a standard deviation of 16.51. Lower leaf count and amounts of iron extracted at higher concentration of iron in the soils are probably due to unset of iron toxicity in the water leaf plants. This indicates that water leaf plants possess great potential in phyto-extraction of iron and other heavy metals from contaminated soil.